Age 7 intelligence and paternal education appear best predictors of educational attainment: The Port Pirie Cohort Study. (22nd December 2014) - Keage, Hannah A.D.; Muniz, Graciela; Kurylowicz, Lisa; Van Hooff, Miranda; Clark, Levina; Searle, Amelia K.; Sawyer, Michael G.; Baghurst, Peter; McFarlane, Alexander
Abstract: Objective: The number of years of education an individual completes is related to their future morbidity and mortality. There are obvious drivers for educational attainment such as childhood intellect, parental intelligence and education attainment, as well as socioeconomic status; and associations may be age‐dependent. We investigated associations between intelligence across childhood (collected at two, four, seven and between eleven and thirteen years) and educational attainment (total years) by the late 20s in the Port Pirie Cohort Study, taking into account maternal intelligence, parental schooling and occupational prestige. Method: There were 388 individuals from the population‐based longitudinal Port Pirie Cohort Study (South Australia) who provided educational attainment data in the 2008‐9 data collection wave. A Structural Equation Model was employed to test associations between educational attainment and childhood cognitive/IQ measures, taking into account parental factors of IQ, schooling and socioeconomic status. Results: The vast majority of variables displayed significant simple correlations with each other in expected directions, e.g. child cognitive/IQ measures with maternal IQ. In the full structural equation model, paternal schooling and child intelligence at seven years were the only variables significantly related to educational attainment by the late 20s; maternal intelligence was strongly associated with early life but not adolescent intelligence. Conclusions: These findings highlight the complex inter‐generational transmission of social advantages, and substantiate the independent effects of education and intelligence on later morbidly and mortality.